ANALISIS TENTANG PENTINGNYA TANGGUNGJAWAB DAN AKUNTANSI SOSIAL PERUSAHAAN (CORPORATE RESPONSIBILITIES AND SOCIAL ACCOUNTING) Studi Kasus Empiris di Kota Medan - Azizul Kholis; Azhar Maksum (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2003)
The objective of this study is to explain affecting factors influenced corporate social responsibility importance by Managerial Perception. Based on Stakeholders theory, the study will investigated social responsibility accounting phenomena on busi-ness practices especially in globalization era. Two regressions models are used to analyze the hypothesis testing. Theoretical framework is replicated from Henriques and Sandorsky's (1999). Data were collected by using questionaires which were mailed to 300 companies in Medan city. There were 67 responses of 54 which were completed and hence usable. Sample are 54 (fifty four) companies in Medan City, North Sumatra. The empirical finding showed that Government regulation, Community pressure, envi-ronmental organization pressure and Mass media pressure are significant factors to corporate social responsibility importance and ifs has positive influenced to social Ac-counting. The impfication of this study is Corporate Social Responsibility Accounting is important issued to discussing in Indonesia.Keywords: Corporate, responsibh'ity, social accounting, managerial perception